A cluster randomized controlled trial examining the effects of a four-week mindfulness-based practice on primary school students’ interpersonal mindfulness, emotional intelligence, and attentional focus - Lin, Li-Jen; Lin, Yu-Hsun; Yu, Su-Ping; Liu, Thu-Hua; Chen, Yi-Lang (Frontiers in Psychology, 2025)
BackgroundAlthough mindfulness benefits are well-established across diverse populations, its impact on primary school children’s interpersonal mindfulness, emotional intelligence, and attentional focus remains underexplored. This study evaluated the effectiveness of a four-week mindfulness-based practice (MBP) intervention among primary school students.MethodsA cluster randomized controlled trial was conducted with 14 classes from Guanghua Elementary School, Taiwan. Classes were randomly assigned to either an intervention group (7 classes, n = 123) or a control group (7 classes, n = 158), encompassing middle and senior-grade male and female students. The intervention group participated in weekly 40-min MBP sessions over 4 weeks. Students completed three validated questionnaires measuring interpersonal mindfulness dimensions (Presence, PR; Awareness, AW; Nonreactivity, NR), emotional intelligence (EI), and mindfulness (MI, attentional focus), using 6-point Likert scales. Assessments were administered at baseline, immediately after the intervention, and at 8-week follow-up.ResultsBaseline scores revealed no significant differences between the groups across all measures. After the 4-week intervention, the intervention group showed significant improvements in PR (p < 0.01), NR (p < 0.01), and MI (p < 0.001) compared to the control group. At the 8-week follow-up, improvements in PR and MI were maintained, while NR gains diminished. Three-way ANOVA identified that gender and grade significantly influenced AW (p < 0.01) and PR (p < 0.05), respectively, with stage effects observed for NR and EI (p < 0.05). Notably, the intervention enhanced AW among boys, and gender-grade interactions had a significant impact on NR and EI outcomes.ConclusionOverall, the four-week MBP intervention significantly enhanced primary school students’ interpersonal mindfulness and attentional focus, with some benefits lasting up to 8 weeks. These findings highlight the importance of tailoring MBP programs to students’ developmental stages and gender-specific needs. Future studies should investigate longer interventions and incorporate objective measures to further validate these outcomes.